ANALYSIS OF SERVICE QUALITY IN APPLICATIONS FOR MAKING PASSPORTS USING M PASSPORTS AT THE CLASS 1 IMMIGRATION OFFICE OF TPI BANDA ACEH - Yuliani, Riska; Husen, Tamitha Intassar (Transpublika Publisher, 2022)
This study aims to determine the Analysis of Service Quality in Applications for Making Passports Using M Passports at the Class 1 Immigration Office of TPI Banda Aceh. In this study, the researcher used a qualitative descriptive approach. The data collection technique in this study was the direct observation method, namely the researcher conducted interviews to obtain information, documentation of data collection such as document recording forms, available notes or documents and documents in the form of images or photos. The research informant method is the subject who provides data in the form of information to the researcher. In this study, the researcher used a purpose sampling technique in which the researcher chose Key Informants and Informants whom the researchers considered to know about the research problem. The place of this research is at the Immigration Office Class 1 TPI Banda Aceh. From the results of the researcher's analysis, Overall, M Passport at the Immigration Office Class 1 TPI Banda Aceh currently provides good benefits in service, queuing passports using M Passport saves time, queuing services are more regular. The simplicity of the service flow using information technology makes it easier for people to get passport-making services and the services provided are clearer and less complicated, while after the M Passport the service is better, people can adjust their arrival schedule. But apart from the researchers found the inhibiting factor for the application of M Passport at the Immigration Office Class 1 TPI Banda Aceh, the inhibiting factor of the application of M Passport was the network, and sometimes M Passport errors.